2021
DOI: 10.1017/s1355617721000473
|View full text |Cite
|
Sign up to set email alerts
|

Residual Effects of Cannabis Use on Effort-Based Decision-Making

Abstract: Objective:Acute Δ9-tetrahydrocannabinol (THC) administration in humans (Lawn etal., 2016) and rats (Silveira, Adams, Morena, Hill, & Winstanley, 2016) has been associated with decreased effort allocation that may explain amotivation during acute cannabis intoxication. To date, however, whether residual effects of cannabis use on effort-based decision-making are present and observable in humans have not yet been determined. The goal of this study was to test whether prolonged cannabis use has residual effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…A study that used a behavioural motivation task, found that an adolescent regular cannabis use sample, switched sooner than controls from a progressive ratio reinforcement schedule based on effortful responses, in exchange for receipt of monetary reward, to a "nonwork" reinforcement schedule (Lane et al, 2005). In contrast, investigation using the EEfRT revealed that a light-using cannabis group chose high effort trials more often than controls (Taylor & Filbey, 2021), translating to increased motivation for monetary reward; this relationship was strengthened among those who report greater cannabis use (Acuff et al, 2022). However, participants under acute cannabis intoxication show significantly decreased effort exertion for reward, compared to placebo (Lawn et al, 2016), in a dose-dependent manner (Wardle et al, 2022).…”
Section: Reward Learning Motivation and The 'Amotivational Syndrome'mentioning
confidence: 99%
“…A study that used a behavioural motivation task, found that an adolescent regular cannabis use sample, switched sooner than controls from a progressive ratio reinforcement schedule based on effortful responses, in exchange for receipt of monetary reward, to a "nonwork" reinforcement schedule (Lane et al, 2005). In contrast, investigation using the EEfRT revealed that a light-using cannabis group chose high effort trials more often than controls (Taylor & Filbey, 2021), translating to increased motivation for monetary reward; this relationship was strengthened among those who report greater cannabis use (Acuff et al, 2022). However, participants under acute cannabis intoxication show significantly decreased effort exertion for reward, compared to placebo (Lawn et al, 2016), in a dose-dependent manner (Wardle et al, 2022).…”
Section: Reward Learning Motivation and The 'Amotivational Syndrome'mentioning
confidence: 99%
“…Previous studies using similar behavioural assessments of motivation have yielded mixed evidence for altered effort-based decision-making for reward in cannabis users, with the three most recent studies finding a positive association between cannabis use and willingness to expend effort for reward on the EEfRT (Taylor and Filbey, 2021;Acuff et al, 2022;Vele et al, 2022). Unlike the EEfRT, rewards in the PhEft are food-based and nonprobabilistic, which could explain the difference in findings.…”
Section: Behavioural Tasksmentioning
confidence: 99%
“…Lane et al (2005) found lower motivation in 14 adolescent cannabis users compared to 20 controls, whereas Lawn et al (2016) did not find a similar effect in 40 adult users and controls. More recently, and using larger samples of 86 participants and 60 participants, respectively, both Taylor and Filbey (2021) and Vele et al (2022) found that adult cannabis users selected hard trials on the EEfRT more often than adult controls. Similarly, Acuff et al (2022) found that frequency of cannabis use and symptoms of cannabis use disorder were positively associated with selecting a high-effort trial in a sample of 47 young adult cannabis users and controls.…”
Section: Introductionmentioning
confidence: 99%